Gender neutral HPV vaccination programs: Reconsidering policies to expand cancer prevention globally - Dykens, J. Andrew; Peterson, Caryn E.; Holt, Hunter K.; Harper, Diane M. (Frontiers in Public Health, 2023)
Human papillomavirus (HPV) infection is responsible for many cancers in both women and men. Cervical cancer, caused by HPV, is the fourth most common cancer among women worldwide, even though it is one of the most preventable cancers. Prevention efforts include HPV vaccination, however these programs remain nascent in many countries. In 2020 the World Health Assembly adopted the Global Strategy for cervical cancer elimination including a goal to fully vaccinate 90% of girls with the HPV vaccine by the age of 15. However, very few countries have reached even 70% coverage. Increased vaccine availability in the future may allow the opportunity to vaccinate more people. This could add to the feasibility of introducing gender-neutral HPV vaccination programs. Adopting a gender-neutral HPV vaccine approach will reduce HPV infections transmitted among the population, combat misinformation, minimize vaccine-related stigma, and promote gender equity. We propose approaching programmatic research through a gender-neutral lens to reduce HPV infections and cancers and promote gender equality. In order to design more effective policies and programs, a better understanding of the perspectives of clients, clinicians, community leaders, and policy-makers is needed. A clear, multi-level understanding of these stakeholders’ views will facilitate the development of target policy and programs aimed at addressing common barriers and optimizing uptake. Given the benefit of developing gender-neutral HPV vaccination programs to eliminate cervical cancer and address other HPV associated cancers, we must build knowledge through implementation research around this topic to inform policy-makers and funders for future policy shifts.